2013
DOI: 10.1017/s1041610213001841
|View full text |Cite
|
Sign up to set email alerts
|

Association of cognitive impairment with frailty in community-dwelling older adults

Abstract: Cognitive impairment was associated with a higher likelihood of frailty in community-dwelling older men and women. Total scores and specific subdomains of cognitive function were inversely associated with frailty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 25 publications
6
51
4
2
Order By: Relevance
“…This discrepancy might be partly explained by participants in the present study being non‐demented and relatively functional without evident impairments in those cognitive domains. However, our observation still concurs with findings from previous large‐scale studies that attention and visual construction were associated with frailty and pre‐frailty . Impairments in visuospatial function can be detected before any other cognitive deficits are observable for age‐related cognitive decline and neurodegenerative disease, which could be a possible explanation of this observation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This discrepancy might be partly explained by participants in the present study being non‐demented and relatively functional without evident impairments in those cognitive domains. However, our observation still concurs with findings from previous large‐scale studies that attention and visual construction were associated with frailty and pre‐frailty . Impairments in visuospatial function can be detected before any other cognitive deficits are observable for age‐related cognitive decline and neurodegenerative disease, which could be a possible explanation of this observation.…”
Section: Discussionsupporting
confidence: 92%
“…The present results showed that visual‐constructional ability and attention were significantly associated with the likelihood of being frail after mutually adjusted for all domains, suggesting that they were driving the relationship between frailty status and cognition. Inconsistently, prior studies observed significant associations of multiple cognitive domains, such as orientation, memory, registration and executive function, with frailty . This discrepancy might be partly explained by participants in the present study being non‐demented and relatively functional without evident impairments in those cognitive domains.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Both cognitive impairment and physical frailty independently lead to increased disability, falls, mortality, an increase in health service need, and high direct/indirect costs to healthcare, often long-term care and hospitalization (Fried et al, 2001; Global Health and Aging, 2015). A growing body of evidence suggests that factors such as mental health and cognition may influence the frailty status of an older adult (Brown et al, 2014; Gray et al, 2013; Han et al, 2014). Frail older adults with cognitive impairment who have a fivefold increase (HR, 5.12) in mortality risk, a twelvefold increase (OR, 12.2) in functional disability, and lower quality of life compared to individuals with isolated frailty or cognitive impairment (Feng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the noncancer setting, the relationship between frailty and cognition was explored in multiple studies . In cross‐sectional studies of older adults, higher odds of cognitive impairment were observed in frail patients as compared with those who are not frail .…”
mentioning
confidence: 99%